Research agendas for the sustainable management of tropical peatland in Malaysia. (28th February 2014) - PADFIELD, RORY; WALDRON, SUSAN; DREW, SIMON; PAPARGYROPOULOU, EFFIE; KUMARAN, SHASHI; PAGE, SUSAN; GILVEAR, DAVE; ARMSTRONG, ALONA; EVERS, STEPHANIE; WILLIAMS, PAUL; ZAKARIA, ZURIATI; CHIN, SING YUN; et al.
SUMMARY: There is a need for coordinated research for the sustainable management of tropical peatland. Malaysia has 6% of global tropical peat by area and peatlands there are subject to land use change at an unprecedented rate. This paper describes a stakeholder engagement exercise that identified 95 priority research questions for peatland in Malaysia, organized into nine themes. Analysis revealed the need for fundamental scientific research, with strong representation across the themes of environmental change, ecosystem services, and conversion, disturbance and degradation. Considerable uncertainty remains about Malaysia's baseline conditions for peatland, including questions over total remaining area of peatland, water table depths, soil characteristics, hydrological function, biogeochemical processes and ecology. More applied and multidisciplinary studies involving researchers from the social sciences are required. The future sustainability of Malaysian peatland relies on coordinating research agendas via a 'knowledge hub' of researchers, strengthening the role of peatlands in land-use planning and development processes, stricter policy enforcement, and bridging the divide between national and provincial governance. Integration of the economic value of peatlands into existing planning regimes is also a stakeholder priority. Finally, current research needs to be better communicated for the benefit of the research community, for improved societal understanding and to inform policy processes.